PENGARUH GREEN ACCOUNTING DAN UKURAN PERUSAHAAN TERHADAP EFFECTIVE TAX RATE : STUDI EMPIRIS PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI NON CYCLICAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2024 - Suryatinna Suryatinna; Nadia Khairany; Eka Nurmayanti; Dyah Ayu Guritno; Elis Hayati; Mahwiyah Mahwiyah (Jurnal Ekonomi dan Manajemen, 2025)
This study examines the influence of green accounting and firm size on the effective tax rate of non-cyclical consumer goods companies listed on the Indonesia Stock Exchange. Using a quantitative approach with secondary data, the research aims to determine whether environmental accounting practices and company scale significantly affect tax efficiency. The findings indicate that green accounting does not have a significant impact on the effective tax rate, suggesting that the disclosure of environmental costs and sustainability activities has not yet influenced corporate tax behavior. Conversely, firm size shows a significant relationship with the effective tax rate, implying that larger firms tend to have more structured tax management and compliance systems. The study highlights the importance of integrating sustainability principles with transparent tax reporting to enhance corporate accountability and stakeholder trust within Indonesia’s evolving green business environment.